1, 6-heptadiynes based cyclopolymerization functionalized with mannose by post polymer modification for protein interaction. (October 2021) - Kumar, Pawan; Kanjilal, Pintu; Das, Rituparna; Dash, Tapan K.; Mohanan, Manikandan; Le, Trong-Nghia; Rao, N. Vijayakameswara; Mukhopadhyay, Balaram; Shunmugam, Raja
Abstract: Carbohydrate functionalized polymers or Glycopolymers have earned a great deal of interest in recent times for their potential biomedical applications. In the present study, a mannose containing glycopolymer was synthesized by cyclopolymerization of malonic acid derivative using second generation Hoveyda Grubbs′ catalyst. Post-polymerization modification was done to install a propargyl moiety. Finally, functionalization of the propargylated polymer with 2-azidoethyl mannoside using azide-alkyne "click chemistry" furnished the target glycopolymer which was successfully characterized using NMR, FT-IR, mass spectroscopy and advanced polymer chromatography. The glycopolymer was found to self-assemble into capsule and spherical shape in water and DMSO respectively and these morphologies were observed through SEM and TEM. Upon interaction with Con A, the mannose containing glycopolymer showed an increment in aggregation induced fluorescence with increasing concentration of the lectin. In vitro cytotoxicity studies on MCF 7 cell line showed 90% cell viability up to glycopolymer concentration of 500 μg/mL. Graphical abstract: Image 1 Highlights: Synthesis of mannosyl glycopolymer. Synthesis of the polymer through cyclopolymerization. Self-assembly of the polymer in capsule and spherical shapes in water and DMSO. Interaction with ConA and detection through fluorescence.